Assessment of sport nutrition knowledge in Singaporean athletes - Muhammad Ibrahim Nasaruddin (Nanyang Technological University, 2020)
Sport nutrition is a key pillar in sport performance, with various benefits that optimises athletic performance. Conversely, poor nutrition may cause low energy availability (LEA), leading to debilitative effects on health and performance factors. Such detrimental effects of LEA are known as Relative Energy Deficiency in Sport (RED-S). Equipping athletes with sports nutritional knowledge (SNK) may benefit athletic performance whilst reducing the possibility of RED-S. Hence, the aim of the study was to assess the SNK and RED-S awareness in Singaporean athletes. A self-reported 45-item questionnaire survey was disseminated online. This survey was inclusive of nine items to collect data on participants’ demographics, a 34-item self-reported Abridged Nutrition for Sport Knowledge Questionnaire (A-NSKQ) to assess NK and two-items to assess RED-S awareness. The A-NSKQ had two sub-sections: General Nutritional Knowledge (GNK) and SNK. Out of 153 collated responses, 112 responses were deemed as valid responses. The mean total A-NSKQ score was 47.2 (12.1) % (mean (S.D.)). The GNK sub-score was 55.8 (15.1) % whilst the SNK sub-score was 43.1 (14.4) %. The results illustrated that the GNK score was significantly higher than the SNK score (p < 0.001). Also, athletes who had formal nutrition education had significantly higher overall scores than those without prior formal nutrition education (p = 0.04). Also, RED-S awareness was severely lacking in Singaporean athletes. Ultimately, there is room for improvement in the athletes’ NK. Tailored nutrition programs can be a possible approach as an intervention measure to ameliorate the gaps in athletes’ SNK.